Penambahan Carboxymethyle cellulose (Cmc) pada Minuman Madu Sari Apel Ditinjau dari Rasa, Aroma, Warna, pH, Viskositas, dan Kekeruhan (Jurnal Ilmu dan Teknologi Hasil Ternak, 2016)
Apple cider honey drink was modified product from fresh honey with apple cider, but there were pectin and tannin in apple cider effected agglutination and needed stabilizier as CMC. The result objective of this study was to know the best consentration of CMC addition in term of taste, aroma, color, pH, viscosity, and turbidity of apple cider honey drink. The experiment design used was completely randomized design consist four treatments and four replications. The treatments were CMC addition P0 (no addition of CMC), P1 (CMC 0.05 %), P2 (CMC 0.1 %), and P3 (CMC 0.15 %). Conclussion of the hedonic test for taste 7.06;Â  aroma 6.61; pH 6.45; lightness (L*) 21.775; redness (a*) 9.4; yellowness (b*) 10.4; viscosity 1.039 Cp; and turbidity 185.750 NTU